Fluidised and Convective Drying Kinetics of Onion Slices - Doharey, D S; Jain, N K; Kumar, Sunil (Journal of Agricultural Engineering, 2009)
Onion (Alium cepa L.) is an important tuber crop widely used for culinary purposes and pharmaceutical industries. Dried onion powder has gained commercial importance in food industry. The fluidized and convective drying techniques were used for dehydration of onion and the effect of temperature and drying mode on the drying of onion slices were investigated. Increase in drying temperature from 50 to 70degree C decreased the drying time from 480 to 360 min under fluidised drying and from 1200 to 900 min under convection drying. Four thin-layer drying equations were investigated for their suitability to describe the drying behaviour of onion slices. The Page model showed the best fit with high values for the coefficient of determination for fluidised and convective drying low values of ?Â² , EMB and ERMS. Activation energy for fluidised and convective air drying was 44.13 and 11.20 kJ.mol?Â¹, respectively. Quality parameters, like colour, water activity and flavour strength were found to be better for fluidised drying compared to convective type. However, the quality of dried onions was superior at 60degree C in both drying modes.